Relative Fat Mass, A Better Predictor of Erectile Dysfunction: Insights From the NHANES 2001–2004 - BoWen Yang; HanYu Wang; Luyi Tang; JiuHuan Feng; ShuFang Hou (American Journal of Men's Health)
Obesity is a significant factor contributing to erectile dysfunction (ED). Early detection of ED generally results in improved treatment outcomes. Our study aims to elucidate the association between relative fat mass (RFM) and ED by analyzing data from the National Health and Nutrition Inspection Survey (NHANES) spanning 2001 to 2004. We used data from NHANES 2001–2004, employing weighted, multivariable-adjusted logistic regression to assess the relationship between RFM and the risk of ED. Additional analyses included subgroup analysis, smooth curve fitting, and threshold effect analysis. Subsequently, the predictive utility of RFM, body mass index (BMI), and waist circumference (WC) for ED was evaluated using the receiver operating characteristic curve and area under the curve (AUC) calculations. A total of 3,947 American male participants were included in this retrospective study within NHANES. Weighted multivariate logistic regression analysis indicated that, after adjusting for potential confounding factors, RFM was positively associated with the risk of ED (OR = 1.03, 95% CI = 1.01-1.05, p  < .001). No significant saturation effects between RFM and ED were observed (all ps  > .05). In addition, RFM demonstrated superior predictive capability for ED (AUC = 0.644) compared with BMI (AUC = 0.525) and WC (AUC = 0.612). Our findings suggest that higher RFM levels are associated with an increased risk of ED, highlighting its potential utility as a predictive marker for this condition.